Sustainable strategies for management of the “false root-knot nematode” Nacobbus spp. - Lax, Paola; Passone, María A.; Becerra, Alejandra G.; Sosa, Ana L.; Ciancio, Aurelio; Finetti-Sialer, Mariella M; Rosso, Laura C. (Frontiers in Plant Science, 2022)
The genus Nacobbus, known as the false root knot nematode, is native to the American continent and comprises polyphagous species adapted to a wide range of climatic conditions. Alone or in combination with other biotic and abiotic factors, Nacobbus spp. can cause significant economic yield losses on main food crops such as potato, sugar beet, tomato, pepper and bean, in South and North America. Although the genus distribution is restricted to the American continent, it has quarantine importance and is subject to international legislation to prevent its spread to other regions, such as the European Union. The management of Nacobbus spp. remains unsatisfactory due to the lack of information related to different aspects of its life cycle, survival stages in the soil and in plant material, a rapid and reliable diagnostic method for its detection and the insufficient source of resistant plant genotypes. Due to the high toxicity of chemical nematicides, the search for alternatives has been intensified. Therefore, this review reports findings on the application of environmentally benign treatments to manage Nacobbus spp. Biological control strategies, such as the use of different organisms (mainly bacteria, fungi and entomopathogenic nematodes) and other eco-compatible approaches (such as metabolites, essential oils, plant extracts, phytohormones and amendments), either alone or as part of a combined control strategy, are discussed. Knowledge of potential sources of resistance for genetic improvement for crops susceptible to Nacobbus spp. are also reported. The sustainable strategies outlined here offer immediate benefits, not only to counter the pathogen, but also as good alternatives to improve crop health and growth.